2019
DOI: 10.1088/1742-6596/1399/3/033118
|View full text |Cite
|
Sign up to set email alerts
|

Practical implementation of Data Envelopment Analysis technology to assess the innovative sustainability of resource-type regions

Abstract: The article is devoted to the modification of the Data Envelopment Analysis (DEA) method to conduct a comparative assessment of the innovative sustainability of resource-type regions. The theoretical basis for the study was the results of the analysis of accumulated foreign experience and current Russian practice on the assessment of sustainable innovative development at the federal and regional levels. Based on the approaches studied, taking into account the identified advantages and disadvantages, the author… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 2 publications
0
4
0
2
Order By: Relevance
“…The cost of processing 10 kg of meat on average, depending on the adopted technology, is 12533.6 rubles, provided that the maral meat is not purchased, but its own is used. When calculating, it was found that in LLC "Rus", animals for meat from 50 to 55 heads were culled annually, on average, 6480 kg of meat was received from them [23][24][25].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cost of processing 10 kg of meat on average, depending on the adopted technology, is 12533.6 rubles, provided that the maral meat is not purchased, but its own is used. When calculating, it was found that in LLC "Rus", animals for meat from 50 to 55 heads were culled annually, on average, 6480 kg of meat was received from them [23][24][25].…”
Section: Resultsmentioning
confidence: 99%
“…Processing of tails is done manually -this is a laborious and rather lengthy process. Processing of maral tails usually consists in drying the tails using a vacuum dryer [19][20][21][22][23].…”
Section: Resultsmentioning
confidence: 99%
“…Для целей данного исследования предлагается использовать понятие «инновационная устойчивость региона» (Ruiga, Stupina, Kovzunova, Chayka, Shkradyuk, 2019). Для определения соответствующей системы показателей и методов количественной оценки эффективности инновационного развития регионов с позиции устойчивости целесообразно взять за основу методологию оценки эффективности инновационной деятельности на федеральном и субфедеральном уровнях.…”
Section: актуальность исследованияunclassified
“…Обобщая преимущества и недостатки научных подходов к оценке инновационного развития и идентификации угроз в иннова-ционной сфере (следуя теории экономической безопасности), наиболее обоснованной с точки зрения практической реализации, по мнению автора, представляется методика на основе формирования интегрального индекса в рамках двух проекций (Ruiga, Stupina, Kovzunova, Chayka, Shkradyuk, 2019): 1) инновационный потенциал региона; 2) результаты инновационной деятельности региона (эффективность инновационного развития). Интегральные индексы (или показатели) формируются с учетом частных показателей, которые предварительно подвергаются простому нормированию на величину расхождения между их фактическими и пороговыми значениями.…”
Section: методологияunclassified
See 1 more Smart Citation